Flow and mixing characteristics of single-pulsed dual parallel plane jets - Y.A. Altaharwah; C.M. Hsu (Results in Engineering)
The flow and mixing characteristics of single-pulsed dual parallel plane jets were experimentally investigated in this study. The smoke flow visualization approach with laser-light sheet assistance was used to analyze the flow evolution processes. The binary boundary edge detection method was used to quantify the jet flow's visual spread. The instantaneous and mean velocities, turbulence intensities, Lagrangian integral time, and length scales were all measured with a hotwire anemometer. The tracer-gas concentration detection approach was utilized to assess the jet fluid's dispersion properties. The lateral distribution of mean velocity vectors and vorticity were assessed using PIV technique. Based on Jets Reynolds number ratio and pulsation intensity two distinct flow modes, the pulsed jet dominating flow and the non-pulsed jet dominating flow could be categorized. The characteristic flow mode at R < 1.0, and Ip < 2.0, is the pulsed jet dominating flow, in which the pulsed jet's vortex drives the non-pulsed jet's vortex. The characteristic flow mode at about 1.0 < R < 2.0, and about Ip < 1.0, is the non-pulsed jet dominating flow, in which the non-pulsed jet's vortex drives the pulsed jet's vortex. The characteristic flow mode reassemble pulsed jet dominating flow at about 1.0 < R < 2.0, and about 1.0 < Ip < 2.0. In the non-pulsed jet dominant flow mode, the overall spread width and concentration reduction index are greater than in the pulsed jet dominant flow mode. With increased pulsation intensity in the pulsed jet dominating flow mode, the spread width, and Lagrangian integral length scale increases, while the Lagrangian integral time scale decrease.